Effects of distinct collybistin isoforms on the formation of GABAergic synapses in hippocampal neurons - Körber, Christoph; Richter, Andrea; Kaiser, Michaela; Schlicksupp, Andrea; Kuner, Thomas; Kirsch, Joachim; Kuhse, Jochen (Molecular and cellular neuroscience, 2012)
Collybistin (Cb) is a brain specific guanine nucleotide exchange factor that interacts with the inhibitory postsynaptic scaffold protein gephyrin. Cb is essential for the postsynaptic clustering of gephyrin and major GABAA receptor subtypes during the formation and maintenance of GABAergic synapses in the hippocampus and other areas of the forebrain. In the rat, four distinct splice variants (Cb1, Cb2SH3−, Cb2SH3+ and Cb3), have been described, which differ in their C-termini (Cb1-3) and in respect of the SH3-domain that is absent in Cb2SH3−. In the human brain, only a single isoform (hPEM2) corresponding to Cb3, was found to be expressed. This has been implicated in neurological defects such as hyperekplexia, epilepsy, anxiety, aggression and mental retardation. In this study, we address the functional significance of the differentially spliced Cb isoforms by generating a shRNA-mediated knock-down of endogenous Cb in hippocampal cultured neurons that is subsequently rescued by the expression of distinct Cb isoforms. We found that the Cb knock-down induced impairment in GABAergic neurotransmission could be rescued by the expression of any of the Cb isoforms, independent of their C-termini or the presence of the SH3-domain in the N-terminal region. Thus, the different Cb isoforms all confer basic functionality.